GLACIOTECTONIC DEFORMATION PATTERNS IN ESTONIA - Rattas M.; Kalm V. (My University, 2004)
Field and archival data have been used in compiling the Glaciotectonic Map of Estonia. Two principal types of glaciotectonic deforma- tions shown on this are discussed here: dislocations of rigid bedrock, and soft bed deformations associated with unconsolidated drift masses. Most bedrock disturbances occur in the narrow zone south of the Baltic Klint and in the tectonically crushed zone where the frac- tured bedrock was easy to break, displace and deform by the moving glacier. Some of the bedrock dislocations are related to ice-marginal deposits of the Late Weichselian Glaciation (Palivere and Pandivere Phases). Most subglacial deformations of soft sediments are simple in style, namely: shear and ductile deformations within a thin layer. The spatial organisation and efficiency of drainage beneath the local ice streams determined the deformational behaviour of sediments at the ice/bed interface. Ice-marginal deposits of the Late Weichselian deglaciation have not been subjected to large-scale compressive deformation. This suggests that most marginal deposits were formed as the result of brief standstills of the ice margin which caused sediment deformation either at the ice margin or beneath the ice sole.
Keywords: Estonia; Quaternary; glaciotectonic landforms and structures; bedrock dislocations; soft sediment deformations; drumlins; Cenozoic::Quaternary; Кайнозой::Четвертичная